Hubungan Persepsi Kesejahteraan Guru PIAUD terhadap Minat Menjadi Guru - Rahman, Zikri; Mastuni, Mastuni (Lembaga Yasin AlSys, 2021)
Perception is an observation process obtained by inferring information and interpreting messages through the five senses into an understanding that forms the basis for experience and knowledge. Welfare is a condition in which a person feels safe, secure, prosperous and can fulfill his life needs accompanied by social appreciation in which he lives. Interest is basically a sense of preference and a sense of attachment to a thing or activity, without anyone telling. This study aims to determine the existence of a positive relationship between perceptions of teacher welfare on PIAUD and interest in becoming a teacher in Senyiur Village. The population of this study is PIAUD teachers in Senyiur Village in 2021, totaling 171 teachers with a sample of 102 respondents. This type of research is descriptive quantitative. The analytical method used is descriptive percentage with simple regression analysis. The results of the analysis obtained an R value of 0.729 with a significance level of 0.005. This means that there is a relationship between perceptions of the welfare of PIAUD teachers and their interest in becoming a teacher in Senyiur Village. Based on these results, it can be concluded that the perception of the welfare of PIAUD teachers on the interest in becoming a teacher has a positive relationship. Therefore, if the view of the welfare of an PIAUD teacher is further raised, the interest of PIAUD teachers to become a teacher will also increase. So the government is expected to pay more attention to the welfare of PIAUD teachers who work at PIAUD institutions where the institutions are more advanced/large (urban areas) and if the salary they receive is much higher than the PIAUD institutions which are still small in scale (rural areas). By having the view that the more prosperous the PIAUD teachers who work in the more advanced/larger PIAUD institutions are, the interest in becoming an PIAUD teacher in the individual will increase.